Metabolite control of enzyme activity links stress to biosynthetic regulation - Wilhelmina van de Ven; Manhoi Hur; María Fernanda Gómez-Méndez; Jingzhe Guo; Haiyan Ke; Raisul Awal Mahmood; Sunghwan Kim; Thomas D. Sharkey; Katayoon Dehesh (Proceedings of the National Academy of Sciences, 2026)
Cells must continuously adjust metabolic output to maintain homeostasis under changing environmental conditions, yet the mechanisms that enable rapid and reversible control of pathway activity remain largely unknown. The methylerythritol phosphate (MEP) pathway, of bacterial origin and conserved in plastid-bearing eukaryotes, including plants and apicomplexan parasites, produces isoprenoid precursors essential for growth and stress adaptation. Here, we identify methylerythritol cyclodiphosphate (MEcPP) as a dual-function metabolite that serves both as a biosynthetic intermediate and a direct modulator of enzyme activity. Genetic perturbations and high light stress revealed step-specific MEcPP accumulation independent of transcriptional regulation. Biochemical and protease-protection assays showed that MEcPP destabilizes and inhibits methylerythritol cytidylyltransferase (MCT) while modestly stabilizing hydroxymethylbutenyl diphosphate synthase (HDS). Molecular docking analyses indicate that MEcPP interacts directly with the MCT catalytic site, displacing the natural substrate and thereby attenuating enzyme activity, suggesting a competitive, feedback-like mechanism of metabolic control. These results define MEcPP as a metabolic feedback signal that translates stress-induced changes into targeted enzymatic control. This mechanism illustrates how pathway intermediates dynamically coordinate biosynthetic activity with environmental cues, representing a broadly conserved strategy for metabolite-driven control of cellular metabolism.